A comparative study of dynamic performance the shear-wall and bracing shapes on the tall building in seismic area - Anwar, Siti Nur Rahmah; Ernanda, Feryan; Sulton, Mohammad; Anwar, Siti Aminah; Anwar, M. Syaibani (Edelweiss Applied Science and Technology, 2024)
The solution to overcome earthquake loads in the seismic regions is to use resisting systems such as shear walls and braces. It can be used as an alternative design for resisting systems of tall buildings. The main purpose of this research is to compare the performance of tall buildings with resisting systems of partial shear walls and a variety of brace shapes in the seismic area of Malang City, Indonesia, by using the partial shear wall against braces of reinforced concrete in the shapes of V, inverted V (Ʌ) and X (on two floors). The mechanical properties of the materials utilized in the models are determined from laboratory testing results. They consist of 30 MPa compressive strength concrete, 250 MPa yield strength steel, and 410 MPa ultimate strength steel. To overcome the lack of bracing, position the braces on the outer side of the building and the number resisting. The several outputs reviewed are stiffness, displacement, drift, ductility, vibration period, and natural frequency. In this study, structural analysis using SAP 2000 v.20 software is used in the four models of the eight-story existing structure in Malang City. The results showed that the inverted V (Ʌ) reinforced concrete brace is the most suitable design as an alternative design for the building, compared to the partial shear wall and the other bracing shapes. The results of the study that in the X-direction the stiffness, displacement, drift, ductility, vibration period, and natural frequency respectively as follows 4.92865E+12 N/mm, 144.53 mm, 127.73 mm, 0.339, 1.12 s and 0.893 Hz. Whereas the displacement and drift in the Y-direction are 127.97 mm and 113.63mm. For practical implication, using a fully shear wall and the inverted V(Ʌ) brace creates a better performance of the structure in seismic areas.